Intensi Berwisata Kuliner Kembali Di Kota Semarang : Suatu Tinjauan Kepuasan Wisatawan - Heri Usodo; Palupiningtyas, Dyah; Agustina Deva PN; Aland Satria AW (E-Bisnis : Jurnal Ilmiah Ekonomi dan Bisnis, 2023)
The research aims to: (1) empirically examine the influence of food quality on tourist satisfaction, (2) the influence of destination image on tourist satisfaction, (3) the influence of destination image on tourist satisfaction, (4) the influence of tourist satisfaction on revisit intention, and (5) the influence of food product quality and destination image on revisit intention through tourist satisfaction. This study adopts a quantitative method. The population of the research consists of tourists who engage in culinary tourism in Semarang city, with a sample size of 125 respondents selected through accidental sampling technique. After reviewing the theory, the research instrument scale is adapted and distributed to the respondents. Once the data is collected, the next step involves data coding. The collected data is then analyzed using Structural Equation Modeling (SEM) to obtain information regarding the influence of the independent variables, namely food product quality and destination image, on revisit intention in culinary tourism with tourist satisfaction as the intervening variable. The results of the research indicate that: (1) food quality empirically influences tourist satisfaction, (2) destination image influences tourist satisfaction, (3) destination image influences tourist satisfaction, (4) tourist satisfaction influences revisit intention, and (5) food product quality and destination image influence revisit intention through tourist satisfaction.